Cancer Dissemination, Hydrocephalus, and Survival After Cerebral Ventricular Entry During High-Grade Glioma Surgery: A Meta-Analysis. Issue 6 (22nd May 2018) - Mistry, Akshitkumar M; Kelly, Patrick D; Thompson, Reid C; Chambless, Lola B
Abstract: BACKGROUND: The consequences of ventricular entry during resection of high-grade gliomas (HGG) are uncertain and often not detectable clinically. OBJECTIVE: To reveal odds of tumor dissemination, hydrocephalus, and mortality in adult patients who had ventricular entry during surgical resection of HGG. METHODS: Titles and abstracts of published journals in the NCBI/NLM PubMed and OVID EMBASE databases were searched without language restriction and systematically screened. Outcomes extracted included the odds of leptomeningeal dissemination and hydrocephalus in patients with ventricular entry during HGG resection compared to without. They were analyzed using a random-effects model to calculate summary odds ratios (sORs). Overall survival data were also compared between patients with and without ventricular entry. RESULTS: Twenty final studies with 2251 total patients were included from the 6910 retrieved. Patients with ventricular entry during HGG resection demonstrated higher odds of leptomeningeal dissemination (sOR: 3.91 [95% confidence interval (CI): 1.89-8.10]; P = .0002; 86/410 vs 57/847 patients in 9 studies) and hydrocephalus (sOR: 7.78 [95% CI: 3.77-16.05]; P < .00001; 58/431 vs 11/565 patients in 11 studies). They also had decreased survival (median survival: 16.8 vs 19.1 mo; 413 vs 322 patients in 10 studies; hazard ratio: 1.25 [95% CI: 1.05-1.48], P = .01). CONCLUSION: The association between ventricular entry during HGG resection and tumor dissemination, hydrocephalus, and decreased survival invites investigations to understand this link. Neurosurgeons and neuro-oncologists must be aware of the consequences of ventricular entry during surgery for HGG.